Tendencies in the explosive strength of the legs within the first year students at the Faculty of Physical Education in the period from 1995 to 2006 year - Jovanovski, Jovan; Vuksanovikj, Vladimir; Regzepagikj A. (Federation of the sports pedagogues of the Republic of Macedonia, 2006)
This research was realized on sample of 1218 students (1016 male and 202 female) from 1995/96 until 2005/06 study year (longitudinal type). The analyzed result are regarding the “horizontal jump-test” within the full time students. The given results are showing that the biggest mean has the male group of students from year of 1999/2000 and the lowest results the group of students from the year 2004/2005. The biggest results of the mean with in the female students is from year 2004/2005 and lowest from year 1995/1996. The analyzes of the frequency, within in the group, for span between 240-320 centimeters, is showing that the most of the students doesn’t have problem to pass the initial check up, which is limited with more than 240 centimeters. The situation it’s same with the female students who also doesn’t have problem to pass the limit of 190 centimeters. From the summary analysis we can say that the trend progression between the average result with in the male and female students it is not in steady-state position. The question about the criteria for entry check-up, for faculty, should emerge from this research.
Тенденции во експлозивната силина на нозете кај студентите од прва година на факултетот за физичка култура во периодот од 1995 до 2006 година
Keywords: explosive power, explosive strength, longitudinal, faculty entry requirements